Root decomposition in grazed and abandoned dry Mediterranean dehesa and mesic mountain grasslands estimated by standard labelled roots - Casals, Pere; Garcia-Pausas, Jordi; Montané, Francesc; Romanyà, Joan; Rovira, Pere (Agriculture, Ecosystems & Environment, 2010)
Because root turnover represents the major source for building up soil organic matter in ecosystems with high belowground allocation, like grasslands, sensitive analyses on root decomposition rates may contribute to point out the effect of grazing abandonment on soil C and N dynamics. The objective was to detect changes in root C and N mineralization due to pasture abandonment in Mediterranean dehesa mountain grasslands. Root decomposition was estimated by ﬁeld incubation of 13 C- and 15 N-labelled wheat roots mixed with unlabelled soil over one year at 5 cm depth in grazed and short-term excluded grasslands in three contrasting situations: (i) a Mediterranean dehesa, (ii) altimontane and (iii) subalpine sites. In addition, the long-term effect of grazing abandonment was estimated in a subalpine shrub encroached site. Overall, root decomposition rates decrease from Mediterranean to mountain sites. Moreover, on mountain sites, either grazing exclusion or shrub encroachment reduced 13 C losses from root–soil bags in about four to seven percentage units; in contrast, such an effect was not detected in the Mediterranean grassland. The dynamics of 15 N derived from root–soil bags was site-dependent without a clear pattern related to site climate or grazing abandonment. In general, the fate of mineralized root-N, leached or immobilized in the surrounding soil, seems to be related to soil variables such as the C:N ratio.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: 13C; 15N; Grazing exclusion; Shrub encroachment; Subalpine grasslands; Tracer techniques